A modified specific barrier model based on new time functions and approach for cracks location on the fault plane: application to the 2008 Iwate–Miyagi earthquake - Rezaei, Mohammad Hadi; Khaji, Naser; Di Maio, Rosa; Emolo, Antonio (Geophysical Journal International, 2021)
SUMMARY Specific barrier method (SBM) is a method used for ground motion generation from a finite fault surface. It is based on a regular distribution of rupturing circular subevents located on the fault plane and random arrival times of the waves generated by those cracks. This approach does not consider the whole rupture kinematics, that is the rupture propagation from the hypocentre to the subevents, and leaves parts of the fault unbroken (barriers). In this paper, we propose a modified version of the SBM for generation of synthetic ground motions from a fault surface. In this version, we modify the probability density function (PDF) for the arrival time of the waves coming from different parts of the fault in order to better account for the fault kinematics and the distance between fault point and receiver. In this way, we can simulate the middle part of the acceleration spectrum (i.e. between 0.1 and 7 Hz) with more accuracy. Moreover, a new arrangement for locating cracks throughout the fault plane is proposed to add flexibility to the model and enable it to make the part of the spectrum with frequency larger than 7 Hz more like what happens in nature. In such an arrangement, called geometry packing in this paper, the size of circles varies within a chosen specific allowable range, while the circles cover all over the fault plane without any overlaps. To validate the proposed modified SBM technique, the synthetic Fourier spectra are compared with recordings of the 2008 Mw6.9 Iwate–Miyagi (Japan) earthquake. Finally, we present some parametric studies to show how different features of the proposed PDFs affect the results from the SBM approach.